Asuhan Keperawatan Pada An.K Dengan Gangguan Sistem Pernapasan: Bronkopneumonia di Ruang Anggrek 2 RSUD Dr. Soeselo Kabupaten Tegal - Farida Erlany; Esti Nurjanah; Ahmad Zakiudin (Jurnal Anestesi, 2024)
Bronchopneumoia is type of pneumonia, namely inflammation of the lungs due to viral, bacterial and fungal infection (Damayanti & Nurhayati, 2019). The purpose of this writing is to find out and provide nursing care to An.K with respiratory system disorders: bronchopneumonia in the anggrek ward 2 RSUD dr.Soeselo Kabupaten Tegall in accordance with nursing standards. The method used is data collection methods in the form of interviews, observation, consultation, examination. From the case review, it was found that An.H’s mother’s main complaint was that An.K was experiencing shortness of breath. Three diagnoses were found, namely ineffective airway clearance, anxiety and knowledge deficit about bronchopneumonia. Interventions are prepared based on the theory of SDK, SLKI and SIKI as well as on the client’s condition and can be implemented.